Complete Remission of Metastatic Neuroendocrine Paragastric Carcinoma After "Neoadjuvant" Peptide Receptor Radionuclide Therapy and Surgery. (August 2015) - Schmidt, Matthias C.; Uhrhan, Klara; Fischer, Thomas; Schmitz, Stephan; Markiefka, Birgid; Drzezga, Alexander; Stippel, Dirk
Abstract : Abstract: A 48-year-old man presenting with upper abdominal pain was diagnosed with neuroendocrine tumor after biopsy of a paragastric mass with multiple liver metastases. 68 Ga-DOTATATE PET/CT showed intense uptake in the paragastric tumor and in multiple liver metastases not allowing primary surgery. Two cycles with cumulative 14.6 GBq 177 Lu-DOTATATE were given resulting in a considerable improvement. Subsequent surgery resulted in a complete remission as demonstrated by 68 Ga-DOTATATE PET/CT. Usually, peptide receptor radionuclide (PRRT) therapy is considered a palliative treatment. Few patients demonstrate a very favorable response allowing resection of the primary tumor after downstaging metastatic disease burden.